Hydroxyde de fer (III) : Chimie de surface et complexation de surface appliquée aux polluants ; le chrome (VI) et l’acide citrique - M’hamed HMAMOU (Faculté des Sciences de Rabat, 2021)
The technique used to determine the sorbent surface parameters PZC and IEP when studying the surface chemistry of iron (III) hydroxide was to follow the initial pH variations of iron (III) hydroxide suspensions as a function of hydration time. Examination of the pH=f (tct) variations and their derivative curves smoothed by polynomial equations allowed the deduction of the values of PZC=7.5±0.1 and IEP = 7.6±0.1. Thus, the potentiometric determination of the suspension with Fe (III) content equal to 40 mg/L shows that the latter presents a basic character with a mass content of active site equal to about 9.3x10-6.
Iron (III) hydroxide: Surface chemistry and surface complexation applied to pollutants; chromium (VI) and citric acid
Keywords: Chimie; Chimie